2013
DOI: 10.3906/zoo-1212-31
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and distribution of eggs and larvae of anchovy (Engraulis encrasicolus, Linnaeus, 1758) and horse mackerel (Trachurus mediterraneus, Steindachner, 1868) on the coasts of the eastern Black Sea

Abstract: Abundance and distribution of eggs and larvae of anchovy (Engraulis encrasicolus, Linnaeus, 1758) and horse mackerel (Trachurus mediterraneus, Steindachner, 1868) on the coasts of the eastern Black Sea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In contrast, aerial surveys performed by the USSR in the 1960s and 1970s have recorded bottlenose dolphins in the deep central part of the basin. Considering the changes to the marine ecosystem in the last few decades, it is suspected that the distribution, migrations, abundance and spawning areas of fish stock in the Black Sea will have been affected at a significant level (Bat et al 2007, Şahin andHacimurtazaoğlu 2013). It is not unrealistic to suggest that the diet of bottlenose dolphins could have been more focused on pelagic fish prior to the fishery collapse in the 1980s and early 1990s than is currently the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, aerial surveys performed by the USSR in the 1960s and 1970s have recorded bottlenose dolphins in the deep central part of the basin. Considering the changes to the marine ecosystem in the last few decades, it is suspected that the distribution, migrations, abundance and spawning areas of fish stock in the Black Sea will have been affected at a significant level (Bat et al 2007, Şahin andHacimurtazaoğlu 2013). It is not unrealistic to suggest that the diet of bottlenose dolphins could have been more focused on pelagic fish prior to the fishery collapse in the 1980s and early 1990s than is currently the case.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological features, changes in fish stocks and migration patterns of commercial fish have been studied by several authors (Chashchin 1996, Daskalov 2003, Radu et al 2011. For example, it has been found that most catches come from areas with water temperature between 10 and 14°C (Agirbas et al 2010), and the highest abundance of fish eggs and larvae during spawning season in Turkish waters was found to be between 10 and 25°C (Satilmis et al 2003, Şahin andHacimurtazaoğlu 2013). In the Istanbul Strait, fish migration was found to occur between 13 and 22°C (Öztürk et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Data for horizontal tows are mean ± standard deviation or a single value is given for single samples. Şahin and Hacimurtazaoğlu (2013) off the coasts of İyidere, and Rize, in the south-eastern Black Sea, Turkey. The spawning period of E. encrasicolus in the Turkish waters runs from May through September (Gordina et al 1997, Şahin andHacimurtazaoğlu 2013, Başar unpublished * , Yüksek unpublished ** ) which was supported by the presently reported study.…”
Section: Discussionmentioning
confidence: 99%
“…Şahin and Hacimurtazaoğlu (2013) off the coasts of İyidere, and Rize, in the south-eastern Black Sea, Turkey. The spawning period of E. encrasicolus in the Turkish waters runs from May through September (Gordina et al 1997, Şahin andHacimurtazaoğlu 2013, Başar unpublished * , Yüksek unpublished ** ) which was supported by the presently reported study. The abundance of E. encrasicolus eggs increased from May through September as the surface water temperatures increased and hence, the most favourable temperature range was 15.5 to 25.3°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation